Some new results for the Srivastava-Luo-Raina $\mathbb{M}$-transform pertaining to the incomplete H-functions - M. K. Bansal; D. Kumar; J. Singh; A. Tassaddiq; K. S. Nisar (AIMS Mathematics, 2020)
The image formula of the incomplete H-functions is derived in this paper by using the Srivastava-Luo-Raina M-Transform. Also, we obtained the image formulae of some useful and important cases of incomplete H-function. The results derived in this paper are in general form and several known and new results can be obtained by giving particular values to the parameters involved in the main results.